Spiritual Well-Being of Senior High School Students in a Non-Sectarian Private High School - Ayrton G. Macainan; Joel M. Bual (Philippine Social Science Journal, 2025)
Rooted in spiritual well-being theory, this quantitative descriptive-comparative study assessed the spiritual health of 75 Humanities and Social Sciences (HUMSS) students at a private non-sectarian school in Northern Negros Occidental during the 2024-2025 academic year. Using a standardized questionnaire and stratified random sampling, the findings revealed that while students exhibited high religious well-being, their existential well-being was moderate, resulting in an overall moderate level of spiritual well-being. Significant disparities were observed specifically in religious well-being, with Catholic students, those from lower-income families, and first or third-born children scoring higher than their counterparts. Consequently, the study recommends establishing a strong values-based culture by integrating spiritual principles into the Introduction to World Religions and Belief Systems (IWRBS) curriculum and enhancing teacher competence in value inculcation. Future research is encouraged to utilize larger samples and varied variables to improve generalizability and depth.